Decreased Tidal Volume May Limit Cardiopulmonary Performance During Exercise in Subacute Stroke. Issue 5 (September 2015) - Sisante, Jason-Flor V.; Mattlage, Anna E.; Arena, Ross; Rippee, Michael A.; Billinger, Sandra A.
Abstract : PURPOSE: The aim of this retrospective study was to determine whether pulmonary function was reduced at submaximal and peak exercise in subacute stroke (SG) when compared with sedentary adults (CON). METHODS: Ten individuals with subacute stroke and 10 sedentary, age- and gender-matched adults performed cardiopulmonary exercise testing (CPET), using a recumbent stepper. We used independent t tests to determine between-group differences at peak effort. We used repeated-measures analysis of variance with Test Minute (minutes 1-6) as the within-subject factor and Group (SG, CON) as the between-subject factor to assess cardiopulmonary submaximal performance. RESULTS: The SG had significantly lower values ( P < .05) for oxygen uptake, minute ventilation ( E), and tidal volume (VT) than CON at peak effort of the CPET. During CPET submaximal effort, we report a significant main effect for Test Minute and Group for VT and respiratory rate but no main effect of Group for E. To maintain adequate E during submaximal effort and decreased VT, higher respiratory rate was observed. CONCLUSIONS: These results suggest that diminished VT in subacute stroke patients may limit performance during submaximal and peak effort of CPET. Rehabilitation professionals should consider methods for improving pulmonary function during stroke rehabilitation. Abstract : We studied individuals with subacute stroke to determine whether pulmonary function was reduced at submaximal and peak exercise compared with controls. Our results suggest that deficits in tidal volume may limit submaximal and peak exercise in subacute stroke patients. Therefore, rehabilitation professionals should consider therapies designed to improve pulmonary function during rehabilitation.